Translation of the Voynich Manuscript using the Differential Abstraction Method. (14th July 2016) - Kim, Milton
Abstract : A partial translation of the Voynich manuscript using the differential abstraction method is presented. This method is used to infer the meaning of Voynich characters or words, identify the probable number system found in the Voynich script, and introduce artificial breaks into a lengthy text to handle each piece separately. The advantage of differential abstraction is that the process of abstraction requires no other verification process to check the validity of the translation results. This is a very useful feature especially for the translation of unidentifiable scripts like the Voynich manuscript of unknown origin with plentiful drawings accompanied by captions. Nonetheless differential abstraction does not guarantee the final translation of the given Voynich characters or words. Instead, it is more likely to provide approximate meaning as stepping stones towards it. With the exemplary paragraph of Folio 2r, differential abstraction can result in the translation of the Voynich manuscript.